Cows in the city: A living from milk - International Livestock Research Institute (International Livestock Research Institute, 2014)
This film tells the story of Sheha Saidi, a dairy farmer from Dar es Salaam, Tanzania, who shares her experiences of the differences between keeping dairy cattle in the city compared to keeping animals in the rural area of Pongwe, Tanga where her sister lives and keeps dairy cows.